Identification the main challenges of small and medium sized enterprises in exploiting of innovative opportunities (Case study: Iran SMEs) - Jahangir Yadollahi Farsi; Mohammad Taghi Toghraee (Journal of Global Entrepreneurship Research, 2014)
The pace of innovation continues to increase not only in the developed world but also in developed markets. The key issue facing many small medium-sized enterprises is related to how they can foster effective innovation. Innovation in SMEs can be (more) efficient and effective; however, this is not the case in many SMEs. SMEs in Iran are industrial and service enterprises with less than 50 employees, because of their size and resource limitations, they are unable to develop new technologies or to make vital changes in the existing ones. The aim of this study is to identify the most important challenges of small and medium businessesa in exploitation of innovation opportunities. We used the exploratory factor analysis which demonstrated the following six challenges in the order of importance: managerial and human resource; research and development; technologies, national policy and regulatory environment and lack of market information.
Keywords: 650; Innovation; SMEs; Innovative opportunities; SMEs challenges